2019
DOI: 10.1016/j.cemconcomp.2019.103395
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of crack self-sealing in cement-based composites with superabsorbent polymers

Abstract: Recently the concept of crack self-sealing has been investigated as a method to prevent degradation and/or loss of functionality of cracked concrete elements. To obtain self-sealing effect in the crack, water swelling admixtures such as superabsorbent polymers (SAP) are added into the cementitious mix. In order to design such self-sealing systems in an efficient way, a three-dimensional mesoscale numerical model is proposed to simulate capillary absorption of water in sound and cracked cement-based materials c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Therefore, the permeability was lower in between SAP macropores in samples containing SAPs than of reference samples. This was also shown by using neutron radiography [35,36] and supported by modeling on mesoscale level [56,57].…”
Section: Changing the Microstructure To Increase The Freeze-thaw Resistance By The Formation Of An Internal Void Systemsupporting
confidence: 56%
“…Therefore, the permeability was lower in between SAP macropores in samples containing SAPs than of reference samples. This was also shown by using neutron radiography [35,36] and supported by modeling on mesoscale level [56,57].…”
Section: Changing the Microstructure To Increase The Freeze-thaw Resistance By The Formation Of An Internal Void Systemsupporting
confidence: 56%
“…The decrease in permeability can be enhanced further by the use of expansive agents [131]. All this information is currently used in threedimensional mesoscale numerical models to simulate capillary absorption of water in sound and cracked cement-based materials containing SAP [54, 132,133]. The experimental results are used as validation and will optimize the application of SAP and the practical applications.…”
Section: Self-sealingmentioning
confidence: 99%
“…Studies have reported on SAP-induced changes in cement composite properties after Jensen et al proposed SAP as a water-entraining admixture for internal curing in high-performance concrete [1,2]. It has been reported that SAPs can reduce the permeability of water through cracks when cracks occur in cement composites [3,4,5,6]. It also has been reported that SAPs heal cracks by supplying moisture to cement composites [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%